2019
DOI: 10.7554/elife.37527
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific maturation profiles of human, chimpanzee and bonobo neural cells

Abstract: Comparative analyses of neuronal phenotypes in closely related species can shed light on neuronal changes occurring during evolution. The study of post-mortem brains of nonhuman primates (NHPs) has been limited and often does not recapitulate important species-specific developmental hallmarks. We utilize induced pluripotent stem cell (iPSC) technology to investigate the development of cortical pyramidal neurons following migration and maturation of cells grafted in the developing mouse cortex. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 54 publications
17
82
0
Order By: Relevance
“…for example, rat dissociated neurons reach stage 3 after approximately 1.5 days in culture, and cortical development in maturation in mammals ranging from mouse to primate is both faster and less complex than in humans (Dotti, Sullivan, and Banker 1988;Clowry, Molnar, and Rakic 2010;Molnar and Clowry 2012;Silbereis et al 2016;Marchetto et al 2019). We found that human iPSC-derived neurons transition to stage 3 in approximately 7 days, which is consistent with the described prolonged development of human neurons in vivo and in vitro (Grabrucker et al 2009).…”
Section: Development Of Polarized and Functional Human Ipsc-derived Nsupporting
confidence: 86%
“…for example, rat dissociated neurons reach stage 3 after approximately 1.5 days in culture, and cortical development in maturation in mammals ranging from mouse to primate is both faster and less complex than in humans (Dotti, Sullivan, and Banker 1988;Clowry, Molnar, and Rakic 2010;Molnar and Clowry 2012;Silbereis et al 2016;Marchetto et al 2019). We found that human iPSC-derived neurons transition to stage 3 in approximately 7 days, which is consistent with the described prolonged development of human neurons in vivo and in vitro (Grabrucker et al 2009).…”
Section: Development Of Polarized and Functional Human Ipsc-derived Nsupporting
confidence: 86%
“…This study complements previous research focused on protein-coding changes [4,6] and helps extend the investigation of species-specific differences in cortical development that has so far relied on detailed comparisons between humans and non-human primates [52,[57][58][59][60].…”
Section: Resultssupporting
confidence: 55%
“…One study, using 2D and 3D stem cellderived cultures, found that differences in neuronal cell numbers among rodents, non-human primates, and humans could be partially explained by the differences in the presence and length of a developmental stage of cerebral cortex progenitor expansion that was significantly increased in humans [111]. Supporting this finding, two studies found that cellular maturation took longer in humans organoids compared to chimpanzee and bonobo organoids [82,110]. Many upregulated genes and changes in DNA accessibility in these studies were identified as being specific to the developing human brain [82].…”
Section: Evolution Of the Human Brainmentioning
confidence: 96%
“…One other interesting emerging application is to study the evolution of the human brain by comparing cultures derived from human to other non-human primates which share many of the transcriptional programs determining cell type in the developing cerebellar cortex [82,83,110,111]. One study, using 2D and 3D stem cellderived cultures, found that differences in neuronal cell numbers among rodents, non-human primates, and humans could be partially explained by the differences in the presence and length of a developmental stage of cerebral cortex progenitor expansion that was significantly increased in humans [111].…”
Section: Evolution Of the Human Brainmentioning
confidence: 99%